Quantitative Analysis of a Pilot Transwell Barrier Model with Automated Sampling and Mathematical Modeling - Júlia Tárnoki-Zách; Szilvia Bősze; András Czirók (MDPI AG, 2023)
In the preclinical phase of drug development, it is necessary to determine how the active compound can pass through the biological barriers surrounding the target tissue. In vitro barrier models provide a reliable, low-cost, high-throughput solution for screening substances early in the drug candidate development process, thus reducing more complex and costly animal studies. In this pilot study, the transport properties of TB501, an antimycobacterial drug candidate, were characterized using an in vitro barrier model of VERO E6 kidney cells. The compound was delivered into the apical chamber of the transwell insert, and its concentration passing through the barrier layer was measured through the automated sampling of the basolateral compartment, where media were replaced every 30 min for 6 h, and the collected samples were stored for further spectroscopic analysis. The kinetics of TB501 concentration obtained from VERO E6 transwell cultures and transwell membranes saturated with serum proteins reveal the extent to which the cell layer functions as a diffusion barrier. The large number of samples collected allows us to fit a detailed mathematical model of the passive diffusive currents to the measured concentration profiles. This approach enables the determination of the diffusive permeability, the diffusivity of the compound in the cell layer, the affinity of the compound binding to the cell membrane as well as the rate by which the cells metabolize the compound. The proposed approach goes beyond the determination of the permeability coefficient and offers a more detailed pharmacokinetic characterization of the transwell barrier model. We expect the presented method to be fruitful in evaluating other compounds with different chemical features on simple in vitro barrier models. The proposed mathematical model can also be extended to include various forms of active transport.